Résultats de scénarios à l’aide d’un modèle à moyen terme de l’économie du Québec - Rabeau, Yves; Morin, Normand (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
In this medium term model of the Quebec economy, output in the various sectors of the economy is determined by demand. The different components of final demand take into account the volume exports of Quebec output to the rest of Canada and to the United States. Employment in the various sectors of the economy is determined by the inverse of production function whereas output is distributed among the different economic agents. Income influences final demand. Prices and wages are in part determined endogenously whereas the labour supply, government expenditures, tax rates are treated exogenously in the forecasting period.The results are generally good and various forecasts are made for the 1978-85 period. Three sets of assumptions define what is called a weak, medium and strong scenario. In all scenarios, we observe a productivity slowdown. If we assume the current trend in the slowdown of the public sector is maintained, employment growth is largely explained by the growth of private sector of the economy. Then, it turns out that in all forecasts, employment growth will allow any significant reduction of the unemployment rate over the forecasting period. Only a major shift in productivity trend which would allow Quebec to take a larger share of the North American market could improve the labour market in the years to come.